From flows to violence - Kalb, Don (Anthropological Theory, 2005)
Recent globalization theory reflected a chain of world historical events since the end of the Cold War. Globalization theories were tools for the making of political alliances between market liberals and political, liberals. From the mid-1990s a broad range of institutionalist social science programs showed that globalization outcomes were often better explained by institutional logics (including cultural ones) than by global flows per se. This is, among others, illustrated by the debate on global inequality data. The emerging debate on empire and imperalism is discussed as a logical offshoot of the globalization discussion just as the phenomenon itself is seen as a likely outcome of an epoch of market-driven globalization. Globalization was predicated on the emergence of a US-led transnational western state structure on behalf of the transnational capitalist class based in finance and the large corporations. Territory and space have become more important rather than less, but the explanation of regional trajectories must now be located more firmly in the interaction between local and global structures. This leads to a new agenda in the social sciences: one oriented toward common interdisciplinary programs with a limited range of core questions - about state formations, class formations, mobilizations, claim making, and associated cultural processes. Programs should be more theory driven, comparative, and in search of explanations of divergent spatial and temporal outcomes of universal process.
Anthropology
Keywords: alliances (international relations); civilization; cultural policy; dual polarization; empire; globalisation; globalization; imperialism; international relations; social sciences & state; transnational capitalist class

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Anthropology; Cultural Studies
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world

Karl Polanyi - Isaac, Barry L. (Edward Elgar Publishing, 2005)
This unique Handbook contains substantial and invaluable summary discussions of work on economic processes and issues, and on the relationship between economic and non-economic areas of life. Furthermore it describes conceptual orientations that are important among economic anthropologists, and presents summaries of key issues in the anthropological study of economic life in different regions of the world. Its scope and accessibility make it useful both to those who are interested in a particular topic and to those who want to see the breadth and fruitfulness of an anthropological study of economics.
Anthropology
Keywords: economic anthropology; economics and finance; social policy and sociology